2015
DOI: 10.1093/oep/gpv003
|View full text |Cite
|
Sign up to set email alerts
|

Expectation errors, uncertainty, and economic activity

Abstract: The aim of this study is to analyze the relationship between uncertainty and economic activity. For this purpose, we use a confidential firm level panel data set (Business Tendency Survey) from Turkey to form three uncertainty measures, namely total, idiosyncratic and aggregate uncertainty. In particular, we construct expectation errors of firms by comparing their survey responses about expectations and realizations on their production volume. Our results reveal countercyclical relationships between our uncert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…The arrival of the 2008 financial crisis has triggered a body of research dedicated to analyse the impact of uncertainty on the economy (Ajmi et al, 2015;Arslan et al, 2015;Atalla et al, 2016;Balcilar et al, 2017;Binder, 2017;Binding and Dibiasi, 2017;Bloom, 2014;Caggiano et al, 2014;Chua et al, 2011;Dovern, 2015;Fernández-Villaverde et al, 2015;Hartmann et al, 2017;Henzel and Rengel, 2017;Karnizova and Khan, 2015;Mitchell et al, 2007;Mokinski et al, 2015;Perić and Sorić, 2017;Sorić and Lolić, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The arrival of the 2008 financial crisis has triggered a body of research dedicated to analyse the impact of uncertainty on the economy (Ajmi et al, 2015;Arslan et al, 2015;Atalla et al, 2016;Balcilar et al, 2017;Binder, 2017;Binding and Dibiasi, 2017;Bloom, 2014;Caggiano et al, 2014;Chua et al, 2011;Dovern, 2015;Fernández-Villaverde et al, 2015;Hartmann et al, 2017;Henzel and Rengel, 2017;Karnizova and Khan, 2015;Mitchell et al, 2007;Mokinski et al, 2015;Perić and Sorić, 2017;Sorić and Lolić, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This is referred to as the option value of waiting. Recent empirical studies generally support the theoretical prediction that uncertainty has negative effects on equipment investment (Leahy and Whited, 1996;Guiso and Parigi, 1999;Ghosal and Loungani, 2000;Ogawa and Suzuki, 2000;Bloom et al, 2007;Baum et al, 2010;Bontempi et al, 2010;IMF, 2012;Kang et al, 2014;Kellogg, 2014;Arslan et al, 2015), R&D investment (Bloom, 2007;Caggese, 2012), and hiring of employees (Ono and Sullivan, 2013;Ghosal and Ye, 2015). 2 Bloom (2009), Bachmann et al (2013), and Leduc and Sill (2013) use macroeconomic time-series data to analyze the effects of uncertainty on GDP, industrial production, and employment, and find large negative effects of uncertainty on these macroeconomic variables.…”
Section: Introductionmentioning
confidence: 78%
“…derived from econometric models (Jurado et al, 2015), 5) subjective uncertainty in forecasting (Boero et al, 2008;Clements, 2008;Morikawa, 2013), 6) dispersion of companies' forecast errors (Bachmann et al, 2013;Arslan et al, 2015), and 7) frequency of newspaper articles regarding policy uncertainty (Baker et al, 2015;Gulen and Ion, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abel et al (2015) and Paloviita and Viren (2014) also assumed that uncertainty is exogenous. Moreover, Bloom et al (2013) found no significant causal impact of industry growth rates on industry uncertainty, Arslan et al (2011) support the exogeneity of uncertainty based on Granger causality tests and endogeneity tests, and Haddow et al (2013) found unidirectional causality from uncertainty measures to confidence indicators.…”
mentioning
confidence: 80%